2009
DOI: 10.1159/000203363
|View full text |Cite
|
Sign up to set email alerts
|

Waist to Height Ratio Is a Simple and Effective Obesity Screening Tool for Cardiovascular Risk Factors: Analysis of Data from the British National Diet and Nutrition Survey of Adults Aged 19–64 Years

Abstract: Objective and Method: To analyse data from the nationally representative National Diet and Nutrition Survey (NDNS) collected in 2000/2001 and to investigate how the BMI and two proxy indicators of central fat distribution, namely the waist circumference and the waist to height ratio (WHtR), are associated with each other and with cardiovascular disease (CVD) risk factors. Results: Screening health risk by BMI alone would ‘miss’ 35% of men and 14% of women who are within the normal BMI range (18.5–25 kg/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
112
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 54 publications
7
112
2
6
Order By: Relevance
“…All blood samples were taken to the Dokuz Eylul University Central Laboratory and an Abbott Architect c16000 auto-analyser was used with its original kits for analyses of blood glucose and serum lipids. Standard blood pressure measurements were taken by skilled physicians and nurses using a validated mercury sphygmomanometer from patients at rest (5-10 min) (24)(25)(26) ; WHR $0?90 (men), $0?85 (women) (27) ; and WHtR $0?5 (2,8,14) .…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…All blood samples were taken to the Dokuz Eylul University Central Laboratory and an Abbott Architect c16000 auto-analyser was used with its original kits for analyses of blood glucose and serum lipids. Standard blood pressure measurements were taken by skilled physicians and nurses using a validated mercury sphygmomanometer from patients at rest (5-10 min) (24)(25)(26) ; WHR $0?90 (men), $0?85 (women) (27) ; and WHtR $0?5 (2,8,14) .…”
Section: Variablesmentioning
confidence: 99%
“…BMI has been used for determining obesity for many years, but within the last two decades measurements of abdominal obesity such as waist circumference (WC), waist:hip ratio (WHR) and waist:height ratio (WHtR) have become more important in defining associations between obesity and cardiometabolic risks (2,3) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…WC is a popular anthropometric index for the measurement of abdominal fat distribution, but the use of WC alone may give overestimate the risk in tall subjects and underestimate the risk in short subjects (Hsieh and Yoshinaga 1999). Many studies have suggested that WHtR may be a simple and practical surrogate of central obesity to identify higher metabolic risks (Hsieh and Yoshinaga 1995a, b;Ashwell et al 1996;Cox and Whichelow 1996;Lin et al 2002;Ho et al 2003;Hsieh et al 2003;Ashwell and Hsieh 2005;Hsieh and Muto 2006;Ashwell and Gibson 2009;Hsieh et al 2010). Several studies, especially among Asian populations, have reported that WHtR predicts the presence of cardiovascular risk factors better than other anthropometric measurements (Hsieh and Yoshinaga 1995b;Lin et al 2002;Ho et al 2003;Hsieh et al 2003Hsieh and Muto 2006).…”
Section: Treatment Of High Blood Cholesterol In Adults 2001mentioning
confidence: 99%
“…Excess intra-abdominal fat is associated with predictors of obesity-related health risk (14)(15)(16)(17) , with the measures waist circumference (WC) and waist:hip ratio (WHR) used as non-invasive and inexpensive methods of assessing abdominal adiposity (18)(19)(20) . These measures correlate closely with BMI and some studies have suggested they may be better predictors of disease risk than BMI itself (16,17,19,(21)(22)(23) . Data from the UK have suggested an increase in abdominal obesity, by 17 % for males and 20 % for females, from 1993 to 2008 (24) .…”
mentioning
confidence: 91%